Sigma-1R–Pom121 axis preserves nuclear transport and integrity in poly-PR-induced C9orf72 ALS - Chun-Yu Lin; Hsuan-Cheng Wu; Ru-Huei Fu; Eddie Feng-Ju Weng; Wen-Chi Hsieh; Tsung-Ping Su; Hsiang-En Wu; Shao-Ming Wang (Neurobiology of Disease)
Nucleocytoplasmic transport disruption contributes to the pathogenesis of C9orf72-associated amyotrophic lateral sclerosis (ALS) and frontotemporal dementia. Among the dipeptide repeat proteins translated from G4C2-repeat RNA, poly-PR is particularly toxic, compromising nuclear envelope integrity and transport. Here, we revealed that poly-PR reduced expression of the nucleoporin Pom121 in NSC-34 cells and in an AAV-mediated poly-PR42 mouse model, resulting in cytoplasmic mislocalization of the neuroprotective transcription factor ATF3 and nuclear envelope damage. Pom121 overexpression restored nuclear ATF3 localization and alleviated poly-PR-induced toxicity. We further identified Sigma-1 receptor (Sigma-1R) as a stabilizer of Pom121 that preserved nuclear integrity and ATF3 function under oxidative stress. Overexpression of Sigma-1R, Pom121, or ATF3 rescued poly-PR-induced cytotoxicity. Our findings defined a protective Sigma-1R/Pom121/ATF3 axis and suggested this pathway as a therapeutic target in C9orf72-linked ALS.